Individualization and self-design technology implementation results for continuing education of teachers - Petrova, М.V., Kotov, S.V., Petrova, N.P.,; N.S, Kotovа,; S.A., Borlakova, (Opción, 2020)
The article presents the results of the study that determines the effectiveness of continuing education of teachers based on continuing education programs that use the idea of individualization and self-design technology via the analysis of scientific and pedagogical literature on the topic of research and pedagogical modeling. As a result, the majority of teachers from the experimental group (84.0%) are satisfied with the results of their training, which is 32% more than the share of teachers in the control group. In conclusion, self-designing is directly related to the processes of self-improvement, self-actualization, self-esteem, expanding the idea of self-designing phenomenon.